PEMANFAATAN SAMPAH PLASTIK DAN ORGANIK DALAM PEMBUATAN PAVING BLOCK MENGGUNAKAN MESIN PRESS - Ubaidillah, zacky; Sumarjo, Jojo; Widianto, Eri; Hanifi, Rizal (Al-Ard: Jurnal Teknik Lingkungan, 2019)
Research has been done on the manufacture and testing of paving blocks with plastic and organic waste materials using a press machine. The purpose of this study is to determine the compressive strength of paving blocks and as a solution for handling waste around us. The results of manual making paving block research with 100% plastic waste, the highest value was 110.4 kg/cm2 and the lowest was 42.2 kg/cm2 and the highest organic mixture was 99.8 kg/cm2 and the lowest was 56.0 kg/cm2. Whereas in the masinal pembutan produce value with 100% plastic waste 113,9 kg/cm2 the lowest value 78,4 kg/cm2. Paving blocks with plastic waste materials are in accordance with SNI quality qualifications. Keywords: plastic waste, organic mixture, paving block, hard test press, machine press.